Air pollution and the pandemic: Long‐term PM2.5 exposure and disease severity in COVID‐19 patients. Issue 12 (30th August 2021) - Mendy, Angelico; Wu, Xiao; Keller, Jason L.; Fassler, Cecily S.; Apewokin, Senu; Mersha, Tesfaye B.; Xie, Changchun; Pinney, Susan M.
Abstract: Background and objective: Ecological studies have suggested an association between exposure to particulate matter ≤2.5 μm (PM2.5 ) and coronavirus disease 2019 (COVID‐19) severity. However, these findings are yet to be validated in individual‐level studies. We aimed to determine the association of long‐term PM2.5 exposure with hospitalization among individual patients infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Methods: We estimated the 10‐year (2009–2018) PM2.5 exposure at the residential zip code of COVID‐19 patients diagnosed at the University of Cincinnati healthcare system between 13 March 2020 and 30 September 2020. Logistic regression was used to determine the odds ratio (OR) and 95% CI for COVID‐19 hospitalizations associated with PM2.5, adjusting for socioeconomic characteristics and comorbidities. Results: Among the 14, 783 COVID‐19 patients included in our study, 13.6% were hospitalized; the geometric mean (SD) PM2.5 was 10.48 (1.12) μg/m 3 . In adjusted analysis, 1 μg/m 3 increase in 10‐year annual average PM2.5 was associated with 18% higher hospitalization (OR: 1.18, 95% CI: 1.11–1.26). Likewise, 1 μg/m 3 increase in PM2.5 estimated for the year 2018 was associated with 14% higher hospitalization (OR: 1.14, 95% CI: 1.08–1.21). Conclusion: Long‐term PM2.5 exposure is associated with increased hospitalization in COVID‐19. Therefore, more stringent COVID‐19 prevention measures may be needed in areas with higher PM2.5 exposure to reduce the disease morbidity and healthcare burden. Abstract : We examined the association between long‐term exposure to particulate matter ≤2.5 μm (PM2.5 ) and coronavirus disease 2019 (COVID‐19) outcomes in 14, 783 COVID‐19 patients diagnosed at the University of Cincinnati Health System. Our results suggested that a 1‐μg/m 3 increase in annual average PM2.5 between 2009 and 2018 was associated with 14%–18% higher odds of hospitalization for COVID‐19. Air Pollution and the Pandemic: Long‐term PM2.5 exposure and disease severity in COVID‐19 patients See related Editorial